Effect of post-harvest calcium treatments on the physicochemical properties of cell wall pectin in nectarine fruit during ripening after harvest or cold storage - Vasilakakis, Miltiadis; Diamantidis, Grigorios; Mignani, Ilaria; Manganaris, George A. (My University, 2005)
The effects of post-harvest dips with calcium salts on the quality attributes of nectarine fruits (Prunus persica var. nectarina Ait. Maxim, cv. ‘Caldesi 2000’) were determined after harvest or in cold storage for up to 6 weeks. Nectarine fruits were harvested at the firm-ripe stage (flesh firmness 70 ± 2 N; soluble solids content 10.5 ± 0.2%) and dipped in deionised water (control) or calcium salts (chloride, lactate or propionate) at two calcium concentrations (62.5 or 187.5 mM). The calcium content of nectarine fruits increased up to 240% in the peel, and up to 31% in the flesh, 1 d after immersion. The increase in calcium content in the flesh was accompanied by increased cell wall calcium, corresponding to a significant increase in the “insoluble” pectin fraction. The highest calcium accumulation in the “insoluble” pectin fraction was attained with 62.5 mM calcium which positively affected fruit firmness. The higher calcium concentration (187.5 mM) resulted in increased calcium in the “water-soluble” pectin fraction which did not appear to contribute to retention of tissue firmness. Additionally, still higher concentrations of calcium lactate and calcium propionate resulted in surface damage, leading to undesirable characteristics during fruit ripening.
Keywords: Apples; Calcium; Bitter pit